Late-Life Depression (LLD) - Yasmin Sabrina; Ridha Tahriani; Diaz Jibriel; Yoga Prawira (Indonesian Publication Center, 2026)
Depression in the elderly is becoming an increasingly important mental health issue as the aging population continues to grow in Indonesia and globally. Older adults are vulnerable to depression due to biological, psychological, and social changes they experience, which are often unrecognized as they are mistakenly considered part of normal aging. Symptoms of depression in the elderly include feelings of sadness, loss of interest, sleep and appetite disturbances, as well as decreased energy and concentration. The prevalence of depression is high, particularly among women, those living alone, or those with chronic illnesses. The etiology of late-life depression is multifactorial, involving psychosocial, medical, neurobiological, and inflammatory factors, and associations with cardiovascular diseases. Its management requires special attention from families, healthcare professionals, and the community for early detection, appropriate treatment, and social support to maintain the quality of life of the elderly.